(untitled) (Journal of Educational Sciences, 2019)
The article deals with the problem of application of art methods in various art services. The authors, analyzing the features of art-pedagogical and art-therapeutic services, come to the conclusion that art therapy does not focus on targeted learning and mastering the skills and abilities in any kind of artistic activity, and in art-pedagogy (developing at the junction of pedagogy and art) - the emphasis is not only on the development of artistic culture and help in finding an approach to the successful mastery of practical skills in various types of artistic activity, but also in the introduction to universal values through their own internal experience, through personal emotional experience, through personal participation in the creative process. According to the authors, the use of elements of art therapy in prevention contributes to the strength ening of protective factors in relation to the possible involvement in a negative environment, including suicidal. In accordance with this, they believe that the more widely represented in society forms of sup port to the population, created on the basis of art methods, the stronger the anti-suicide barrier. Summing up the experience of existing centers and services practicing art pedagogy and art therapy with different categories of people, ATORS reveal the specifics of the problem of overcoming communi cation barriers, maladaptation, assistance to children with special educational needs, etc. The analysis of the state of art-pedagogical and art-therapeutic services in Kazakhstan, conducted with the help of a survey of students of schools and universities, allows them to draw a conclusion about the lack of representation of this sphere of psychological services. Art therapy in contrast to art-pedagog ical activity is more widely represented in the market of educational and psychological services, but due to certain circumstances (high cost, weak advertising, etc.) young people do not use them. The authors are convinced that the prevention of suicidal behavior of Kazakh youth is not related to art activities, although the content of the analyzed services may well meet the requirements of suicide prevention. In conclusion, the authors come to the conclusion that in the Republic of Kazakhstan art therapeutic and art pedagogical services are in the initial stage. Key words: art education, art therapy, art techniques, art educational services, art therapy services.